Regional Sustainable Development Strategies in Russia: the Case of the Volga Region - Kirillov, Sergey; Nikonorov, Sergey; Pakina, Alla (European Journal of Sustainable Development, 2019)
In the context of reduced revenues from raw materials exports, the policy of sanctions and restrictions on access to capital and technologies, Russia faces an acute problem of finding new models of economic development. As world experience shows, economic growth cannot resume simultaneously throughout the country, it will inevitably be concentrated in specific regions – points of growth. Since the Federal government do not present a convincing strategy, some regions take the initiative and build their own development strategies. In this regard, the experience of the Volga region with a developed economy, the powerful drivers of growth, and large differences in social parameters is quite interesting. The main development goals were indicated in the Strategy of Privolzhsky Federal district’s development up to 2020. We analyzed them on the example of 7 subjects of Federation. Despite ambitious plans, the negative dynamics of many indicators remains. The growth of GRP has not reached the planned values, and social indicators continue to decline: there is a migration outflow of population and a decrease in natural population growth. Analysis of the each region’s strategies showed that there are significant risks of development, the overcoming of which requires non-trivial decisions of regional governments. Keywords: development strategies, growth points, regional governments, sustainable development, social risks